Cognitive impairment is associated with cardiovascular remodeling in the mouse model of Alzheimer's disease. (20th December 2022) - Haghkar, Mahdi; Grigorova, Yulia N; Cezayirli, Defne; Morrell, Christopher H; Camandola, Simonetta; Petrashevskaya, Natalia; McDevitt, Ross A; Zernetkina, Valentina; Juhasz, Ondrej; Wei, Wen; Mattson, Mark P; Lakatta, Edward G; et al.
Abstract: Background: Double‐mutant mice (APPswe/PS1dE9; 2xTg‐AD) represent a model of Alzheimer's disease (AD). 2xTg‐AD mice develop progressive accumulation of amyloid plaques and cognitive impairment (CI) with age in >12 months old animals. The aim of the present study was to investigate the associations of CI and cardiovascular function in 2xTg‐AD mice. Methods: Aortic pulse wave velocity (aPWV), an estimation of aortic stiffness, and cardiac parameters were measured by echocardiography in 16‐mo old male 2xTg‐AD (n=11) and wild type (WT; n=17) mice. Spatial memory (using Morris water maze; MWM) and the anxiety level (using open field test; OFT) were assessed. The relationship between cardiovascular and behavioral parameters were modeled using a linear regression analysis (LRA) with a backward elimination. P‐values <0.05 were considered significant, and 0.05≤P<0.1 were considered near significant and were included in the models. Results: 2xTg‐AD mice exhibited an increase in aPWV and had a thicker left ventricle (LV) posterior wall in diastole (LVPWd) and narrower LV internal diameter (LVIDd) vs. WT mice (Table 1). 2xTg‐AD mice spent less time in the center of OF vs. WT mice (Table 1). LRA revealed a negative association between time spent in the center of OF and LVPWd, and a positive association with LV volume in diastole (LVvold) in 2xTg‐AD mice (Table 2). In MWM, 2xTg‐AD mice exhibited impaired spatial memory estimated as prolonged average escape latency during their training vs. WT counterparts (Table 1). Although there was no difference between performance in the MWM probe trial, LRA showed a negative association between LVPWd and the mean distance from the platform in the probe trial in 2xTg‐AD mice, and a positive association of LVPWd with number of entries to the platform zone (Table 2). There was a positive association between aPWV and mean distance from the platform in the probe trial in both 2xTg‐AD and WT mice. Conclusions: LRA results indicate that LV remodeling is associated with anxiety‐like behavior in 2xTg‐AD mice, but not with spatial memory impairment. Positive association of aPWV with spatial memory impairment in both groups suggests that aortic stiffness contributes to the age‐associated CI. Supported by the NIH/NIA IRP.